Creating Easy Tender App for Tender Process Procurement Division at PT. United Tractors - Imran, Farhan Ryanda; Pamungkas, R Wisnu Prio (J-INTECH (Journal of Information and Technology), 2024)
In the ongoing era of digital transformation, the use of information technology has become essential in digitizing business processes across various sectors, including the tender process for procuring goods and services. Manual tender processes often face several challenges, such as being time-consuming, prone to human errors, and inefficient. In the Procurement and Investment Function Division 1 of PT. United Tractors, the tender process for optional safety device items is still conducted manually, creating complexity and consuming a significant amount of time. This research proposes the development of an Android-based application, named Easy Tender, to automate most stages of the tender process. The application is designed to include features such as participant registration, tender participant confirmation, automatic winner determination based on the lowest price and set deadlines, and sorting ranking in the tender recap using the Bubble Sort algorithm. Additionally, the application provides ease of digitalized negotiation and allows real-time monitoring of the tender process. With the development of Easy Tender, it is expected that the Procurement and Investment Function Division 1 of PT. United Tractors can digitize their tender processes, making the tender process more efficient, time-saving, and reducing the risk of human errors. This application is also expected to enhance accountability in determining the winner based on the lowest price. Therefore, this research holds high urgency in efforts to improve operational efficiency and the application of information technology in the business world.